Comparison of quality attributes of minced beef samples thawed by ohmic and conventional methods. Issue 2 (9th December 2020) - Cevik, Mutlu; Icier, Filiz
Abstract: Frozen minced meat samples having different fat contents (2%, 10%, or 18%) were thawed using two different standard thawing methods (RT: +4°C refrigeration thawing, URWT: +4°C under running water thawing), and a novel alternative method (ohmic thawing‐OT at voltage gradients of 10, 13, and 16 V/cm). The drip loss values of meat samples changed in the range of 0.01%–1.65%. For OT, the change in the color increased as the fat content increased. OT shortened the thawing time, on average, by 64% and 87% compared to URWT and RT, respectively, while it resulted in similar effects on proximate composition and microbiological load with standard thawing methods. This novel thawing method did not cause any mutagenic formation, and the metal migration was in allowable limits. It is thought that the results showed that OT method has the potential to be applied as a novel alternative method for thawing of meat products. Practical applications: For long‐term storage of meat and meat products, freezing is commonly used. However, frozen food must be thawed before use. For this reason, two different conventional thawing methods were recommended by US‐FDA. However, conventional thawing methods have some disadvantages such as long process times, high energy consumptions, and waste water formation. Ohmic thawing has shorter process time, high energy efficiency, and does not produce any waste water. In this study, frozen minced meat samples (with fat content of 2%, 10%, or 18%) were thawed using different thawing conditions (RT, URWT, and OT at voltage gradients of 10, 13, and 16 V/cm). OT shortened the thawing time. Drip loss was found to be high for OT. The effect of OT on microbiological load and proximate composition was not different from conventional thawing. OT method did not cause any mutagenic formation.